Revealing the impact of tadalafil-loaded proniosomal gel against dexamethasone-delayed wound healing via modulating oxido-inflammatory response and TGF-β/Macrophage activation pathway in rabbit model. - Nermin A Helmy; Elsayed A Abdel Aziz; Mustafa Abd El Raouf; Reda M S Korany; Doaa A Mansour; Sara M Baraka; Arwa A Hassan; Eman Gomaa; Mennatullah M Faisal; Walaa A A Basha; Esraa M Fahmy; Rashed A Alhotan; et al. (PLoS ONE)
A serious challenge of the chronic administration of dexamethasone (DEX) is a delay in wound healing. Thus, this study aimed to investigate the potential of Tadalafil (TAD)-loaded proniosomal gel to accelerate the healing process of skin wounds in DEX-challenged rabbits. Skin wounds were induced in 48 rabbits of 4 groups (n = 12 per group) and skin wounds were treated by sterile saline (control), TAD-loaded proniosomal gel topically on skin wound, DEX-injected rabbits, and DEX+TAD-loaded proniosomal gel for 4 weeks. The optical photography, transmission electron microscopy, in vitro release profile, and stability studies revealed the successful preparation of the selected formula with good stability. DEX administration was associated with uncontrolled oxido-inflammatory reactions, suppression in immune response in skin wounds, and consequently failure in the healing process. TAD-loaded proniosomal gel-treated rabbits manifested a marked enhancement in the rate of wound closure than control and DEX groups (p < 0.05). The TAD-loaded proniosomal gel successfully antagonized the impacts of DEX by dampening MDA production, and enhancing total antioxidant capacity, coupled with modulation of inflammatory-related genes, inducible nitric oxide synthase, tumor necrosis factor-alpha, interleukin-1β, and matrix metalloproteinase 9, during all healing stages (p < 0.05). This was in combination with significant amplification of immune response-related genes, CD68 and CD163 (p < 0.05). Moreover, the histopathological, Masson's Trichrome-stain, and immune-histochemical studies indicated a successful tissue recovery with the formation of new blood vessels in groups treated with TAD-loaded proniosomal gel, as manifested by well-organized collagen fibers, upregulation of transforming growth factor β1, and vascular endothelial growth factor immune expression in skin tissues (p < 0.05). Overall, the topical application of TAD-loaded proniosomal gel is useful in improving the delayed wound healing linked to DEX therapy via regulating the release of inflammatory/macrophage activation mediators and enhanced antioxidant capacity, angiogenesis, and vascularity.